OFFICIAL DEVELOPMENT ASSISTANCE IN COLOMBIA: CHANGES AND CONTINUITIES OF THE PEACE AGREEMENT. CASE STUDY OF THE UNITED STATES AND THE EUROPEAN UNION (2012-2021) (Studia Politica. Romanian Political Science Review, 2025)
The objective of this research article is to conduct the identification of the possible changes and continuities presented in the dynamics and the Official Development Assistance (ODA) received by Colombia from the United States of America and the European Union, after the signing of the Peace Agreement between the government and the Revolutionary Armed Forces of Colombia - People's Army (FARC-EP). A qualitative case study methodology is used by consulting databases and information from official sources on ODA projects granted to Colombia. The period 2012-2021 was set at four years prior to the signing of the agreement and five years after it. The results show significant changes in the amounts and number of projects financed by the United States and the European Union since the signing of the Agreement.
Keywords: International Cooperation for Development; Peace Agreement; Official Development Assistance; Negotiation Process; Colombia